2013
DOI: 10.1007/s13762-013-0237-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental evaluation of alternative chemicals to methyl bromide for fumigation of quarantine pests in transit

Abstract: The majority of recent quarantine schedules have relied on methyl bromide fumigation. However, due to the phase-out of this fumigant in January 2005 alternative treatments are needed. Four alternative chemical fumigants were tested for their potential to replace methyl bromide as a control agent for Bemisia tabaci, Liriomyza huidobrensis and Frankliniella occidentalis. Phosphine at 2 g/m 3 gave promising results at 15°C with complete mortality of all insects after 24 h exposure. Sulphuryl fluoride, ethyl forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Lee et al [ 23 ] reported a high mortality rate of 62.4% for Sitophilus oryzae (mixed age) treated with 67.4 mg/L EF for 6 h. These high concentrations render EF are economically disadvantageous for use in the field. However, studies examining the combination of PH 3 + EF against Aphis gossypii , Lipaphis erysimi , Myzus persicae , Planococcus citri and T. urticae showed that the combined treatment required reduced fumigant concentrations and treatment times compared to individual fumigant treatment [ 17 , 32 , 33 , 34 , 35 ]. This study investigated the insecticidal effect of PH 3 + EF against L. serricorne using a range of EF concentrations, and treatment at 50 mg/L EF for 4 h showed a mortality rate of 88% or more for all stages.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 23 ] reported a high mortality rate of 62.4% for Sitophilus oryzae (mixed age) treated with 67.4 mg/L EF for 6 h. These high concentrations render EF are economically disadvantageous for use in the field. However, studies examining the combination of PH 3 + EF against Aphis gossypii , Lipaphis erysimi , Myzus persicae , Planococcus citri and T. urticae showed that the combined treatment required reduced fumigant concentrations and treatment times compared to individual fumigant treatment [ 17 , 32 , 33 , 34 , 35 ]. This study investigated the insecticidal effect of PH 3 + EF against L. serricorne using a range of EF concentrations, and treatment at 50 mg/L EF for 4 h showed a mortality rate of 88% or more for all stages.…”
Section: Discussionmentioning
confidence: 99%
“…Introduced as a pesticide in 1932 and registered in the United States in 1961, MBr has been widely used as a soil fumigant in tomato production systems in Florida since the late 1970s to control weeds and to manage a variety of other soil-dwelling pests, including nematodes, fungi, and insects (Carpenter et al, 2000;Ristaino & Thomas, 1997). Since MBr was phased out in 2005 as an ozone-depleting substance, alternative chemical fumigants (Cuthbertson et al, 2013;Leon et al, 2009;Qiao et al, 2015;Rosskopf et al, 2005;Schneider et al, 2006) and nonchemical alternatives have been explored (Fernandez-Bayo et al, 2018;Rosskopf et al, 2005Rosskopf et al, , 2020. Chloropicrin and 1,3-dichloropropene are two primary chemical substitutes for MBr and often are used in a mixture to enhance the efficacy of control against soil-borne pests and diseases (Minuto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%